2006
DOI: 10.1021/jf0622883
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotection of Vitamins in Skimmed Milk by an Aqueous Soluble Lycopene−Gum Arabic Microcapsule

Abstract: Riboflavin (Rf)-mediated photosensitized degradation of vitamins A and D3 in skimmed milk under illumination with a white fluorescence lamp was studied by using the HPLC technique. The photosensitized degradation of both vitamins followed first-order kinetics, and the temperature effect on the observed photodegradation rate constant allowed the determination of the activation energy Ea as being 4 and 16 kcal/mol for vitamins A and D3, respectively. The addition of lycopene microencapsulated by spray-drying wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 34 publications
1
29
0
5
Order By: Relevance
“…The high encapsulation efficiency indicates that the majority of the Lyc in the suspension was present in the nanocapsule structures. Montenegro et al (2007) obtained Lyc microcapsules in gum arabic with 95 % encapsulation efficiency, and Silva et al (2012) obtained Lyc microcapsules in a gelatinpectin complex with 93.2 % encapsulation efficiency. However, the encapsulants chosen, such as gelatin, gum arabic, gellan gum, and maltodextrin, can affect the encapsulation efficiency Rodriguez-Huezo et al 2004;Shu et al 2006).…”
Section: Preparation and Physicochemical Characterization Of Lncsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high encapsulation efficiency indicates that the majority of the Lyc in the suspension was present in the nanocapsule structures. Montenegro et al (2007) obtained Lyc microcapsules in gum arabic with 95 % encapsulation efficiency, and Silva et al (2012) obtained Lyc microcapsules in a gelatinpectin complex with 93.2 % encapsulation efficiency. However, the encapsulants chosen, such as gelatin, gum arabic, gellan gum, and maltodextrin, can affect the encapsulation efficiency Rodriguez-Huezo et al 2004;Shu et al 2006).…”
Section: Preparation and Physicochemical Characterization Of Lncsmentioning
confidence: 99%
“…As an antioxidant, Lyc has a singlet-oxygen-quenching ability that is twice that of b-carotene and 10 times higher than that of atocopherol (Silva et al 2012). However, some studies have shown that encapsulation techniques increase the stability of Lyc in the presence of oxygen, heat, and light (Chiu et al 2007; Goula and Adamopoulos 2012;Montenegro et al 2007;Blanch et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Montenegro et al, (2007) determined that the photosensitized RF-mediated degradation of vitamins A, D 3 , and RF itself in skimmed milk was strongly reduced by the addition of small amounts of lycopene-gum arabic-sucrose microcapsules, prepared by spray-drying. Under these conditions, the bulk properties of the skimmed milk were unmodified.…”
Section: Figure 1bmentioning
confidence: 99%
“…In addition, carotenoids are also able to quench the excited triplet state of sensitizers, which are relevant species in the oxidation of lipids, vitamins and proteins (Montenegro, Nunes, Mercadante, & Borsarelli, 2007;Montenegro et al, 2004). Carotenoids also act as scavengers of free radicals (Bohm, Puspitasari-Nienaber, Ferruzzi, & Schwartz, 2002;Miller, Sampson, Candeias, Bramley, & Rice-Evans, 1996;Re et al, 1999).…”
Section: Introductionmentioning
confidence: 99%